Analysis of dynamic size effect of recycled concrete using base force element method. (3rd August 2022) - Peng, Yijiang; Zakaria, Semaoui; Ying, Liping; Cao, Wei; Yang, Hongming; Sun, Yucheng
Abstract: A 2D meso models of recycled concrete with different sizes is established using the base force element method. The specimens are loaded with different strain rates. The meso damage of recycled concrete is analyzed. In addition, the structural performance of specimens under the joint actions with strain rate and size are also studied. The simulation results find that the compressive strength has little difference when the values of strain rates are lower than 0.1 s −1 . The greater the strain rates, the greater the difference of compressive strength between different sizes when strain rates are larger than 0.1 s −1 . In addition, the Bažant statistical theory can be used to analysis the mechanical properties of recycled concrete. Besides, a modified formula in calculating the dynamic size effect of recycled concrete is also given based on the Bažant statistical size effect theory.